Investigation Study on the Strength Properties of Local Sand as Proppant - Priveetha Manogaran, Priveetha (Universiti Teknologi Petronas, 2012)
This project presents literature review and experimental work on local sands for possible use as proppant especially sand samples from the Terengganu coastal area. Currently, there is no local proppant manufacturer in Malaysia and Malaysia has to import proppant from overseas especially from United States and Canada. This leads to the high well stimulation costs in Malaysia. If the local sand in Malaysia qualifies to be used as proppant, Malaysia can produce its local proppant manufacturer which may reduce the well stimulation costs in Malaysia. Thus, in this project, the characteristics of the Terengganu local sand will be examined and compared to the characteristics of the existing proppant used in current market. The present study found that the size distribution, sphericity, turbidity and bulk density of Terengganu sands are at similarity with some of commercial proppants. Thus, in this project additional research and experimental work will be done to further identify the possible use of Terengganu sand as proppant. These samples will be tested upon the sphericity, roundness, bulk density, shear strength, turbidity, acid solubility and suspension of particles in the slurry.